PELATIHAN PEMBUATAN LKPD INOVATIF DISCOVERY LEARNING BERBASIS APLIKASI SCRACTH BAGI MAHASISWA PGSD - Anindyta, Amalina Mutiara; Kusuma, Betania Cahaya; Pramunendya, Wulan Wilanten Dyah; Ferryka, Putri Zudhah (LPPM Universitas Widya Dharma Klaten, 2024)
In this era of digitalization, in addition to students who are required to keep up with the flow of development, educators do not escape the demands of the same responsibility to be more professional, more reliable, more competent in mastering technology. In this era it is quite appropriate if only this technology mastery skill begins to be utilized as a means to improve teacher expertise. One of them is by developing a digital application-based LKPD with Scratch which contains programming material with a teaching focus on mathematics subjects as a form of effort to disseminate a product or work that can be enjoyed for its usefulness. The method used in the process of implementing activities has five stages: 1) preparation and organization, 2) preparing the schedule, materials, and training instruments, 3) implementation of training activities, 4) mentoring and preparation of Discovery Learning LKPD based on scratch application, and 5) evaluation. The results of the training activities show that the overall participant feedback form obtained an average percentage of 86% in the very good category, with an effectiveness rate of 91,7% in the effective category. This shows that the training activities can be followed well by UNISRI and UNS student participants, this has an effect on increasing participants' understanding and skills about making scratch application-based Discovery Learning LPDs before and after attending training so that participants can produce scratch application-based Discovery Learning LPD products to support the learning process.